Evaluating children's writing : a handbook of grading choices for classroom teachers - Bratcher, Suzanne (L. Erlbaum, 2004)
Evaluating Children's Writing: A Handbook of Grading Choices for Classroom Teachers, Second Edition introduces and explains a wide range of specific evaluation strategies used by classroom teachers to arrive at grades and gives explicit instructions for implementing them. Samples of student writing accompany the instructions to illustrate the techniques, and an appendix of additional student writing is provided to allow readers to practice particular evaluation strategies. More than just a catalog of grading options, however, this is a handbook with a point of view. Its purpose i.